Essentials of cognitive grammar - Langacker, Ronald W. (Oxford University Press, 2013)
Ronald W. Langacker created an approach to linguistics called Cognitive Grammar, which is essentially a system of symbols that can be used to organize and analyze how semantics and phonology interact with each other in human language. Cognitive Grammar lays the groundwork for cognitive linguistics, which has become a major sub-field over the past 30 years. Langacker's 2008 OUP book Cognitive Grammar is the authoritative introduction to CG. But for an introduction it's rather long-584 pages, divided into four sections, two of which are truly introductory and two of which offer a more detailed methodology for researchers. This abridged version of Cognitive Grammar makes the two introductory sections available for course adoption at a reduced price. It will reinvigorate this copyright by tailoring it to the course market that has become its primary audience, and by positioning Langacker's authoritative work as an accessible, attractive cornerstone of cognitive linguistics as the field continues to evolve.